Implementasi Metode Pembiasaan dalam Menanamkan Nilai-Nilai Moderasi Beragama pada Anak Usia Dini - Irwandi Irwandi (Lembaga Pengembangan Kinerja Dosen, 2024)
Religious moderation in early childhood is an effort to instill moderate religious values ​​in children from an early age. These values ​​include an attitude of tolerance, being fair, balance and also an attitude of equality. One way to instill the values ​​of religious moderation in young children is through the habituation method. This research aims to find out how the habituation method is implemented in instilling the values ​​of religious moderation in early childhood at Kartika Kindergarten Banda Aceh. What will be discussed in this research is how to implement the habituation method in instilling the values ​​of religious moderation in early childhood at Kartika Kindergarten Banda Aceh. This research uses descriptive qualitative research. Data collected through interviews and documentation. The data obtained will be analyzed descriptive qualitatively. The research results showed that the forms of implementation of the habituation method in instilling the values ​​of religious moderation in Kartika Kindergarten Banda Aceh were ablution, prayer practice, repeating and memorizing short surahs and daily prayers, introduction to places of worship from various religions. Apart from that, learning is carried out by instilling values ​​such as honesty, courtesy, mutual help and mutual respect. The steps for implementing the habituation method in instilling the values ​​of religious moderation in children at Kartika Kindergarten Banda Aceh include teachers as models, preparing learning tools, involving parents, holding religious activities.